Managing decline : a research overview - Sihvonen, Antti, 1983-; Lamberg, Juha-Antti; Tikkanen, Henrikki (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"A growing body of literature in the area of business administration has focused on the phenomenon of decline. These studies span multiple levels of analysis and draws on a range of disciplines, including strategic management, economics, and economic geography. Managing Decline: A Research Overview provides a summary of this research by focusing on three key levels of analysis: industries, clusters, and organizations. The targeted reviews in this book map each individual level of analysis separately and the discussion section outlines overarching themes regarding decline and its management. The three levels are analysed by identifying different forms, causes, processes, and management options regarding decline. This is accompanied by the identification of key academic discourses that have been used to analyse decline. The discussion section highlights broader themes regarding the nature and management of decline that span across the different levels of analysis. This book provides an easy to access summary on the nature and management of decline for academic scholars and business practitioners, and is essential reading for getting an overview of this broad field of research"--
OCLC-licensed vendor bibliographic record.
Keywords: Business -- Research; Management -- Research; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Organizational Behavior